Kontribusi Adversity Quotient terhadap Kecemasan pada Siswa Kelas XII dalam Persiapan Ujian Masuk Perguruan Tinggi Negeri - Syafira, Afifa Putri; Susanti, Roza Eva (Lembaga Yasin AlSys, 2025)
This study investigates the contribution of adversity quotient to anxiety among twelfth-grade students preparing for the state university entrance examination. The preparation process for admission to state universities (PTN) frequently constitutes a substantial source of psychological pressure for students, primarily due to intense competition, restricted admission quotas, and external expectations from the surrounding environment. This research employed a quantitative methodology witha correlational design. The sample comprised 389 students in the city of Padang, selected using a simple random sampling technique. The findings of a simple linear regression analysis demonstrated a significant negative contribution of adversity quotient to anxiety, with a significance value of .000 (p < .05). Furthermore, the coefficient of determination (R²) was reported at .489, indicating that the adversityquotient variable contributes 48.9% to the anxiety experienced by students in the context of university entrance preparation. Therefore, the higher the level of adversity quotient in twelfth-grade students, the lower their level of anxiety in facing the examination.